From Global Decisions and Local Changes: The ceremonial dance of the Voladores becomes UNESCO intangible cultural heritage - Schöneich, Svenja (Ethnologies, 2014)
This paper analyses the transforming effects the “UNESCO intangible cultural heritage” label has on a cultural practice. It uses as a case study the ritual ceremony of the Voladores, an indigenous ritual dance practiced in different areas of Mexico since pre-colonial times. In 2009, it was declared the second of seven UNESCO intangible cultural heritages in Mexico. The following study examines ways in which perceptions and performance of the dance have changed after the declaration from an actor’s perspective. After the declaration the national and international interest of tourist and institutions increased. As a consequence, dancers were able to earn a significant amount of money and gain social recognition through public presentations of the dance, which transformed the ritual into an economic and social resource. On the one hand, the new function changed the ceremony in ways to make it more attractive to tourists. On the other hand, a tendency towards revitalizing and preserving traditional elements came to play as well. This was partly initiated through the UNESCO Safeguarding guidelines and pushed by many dancers afraid of a potential “sell-out of their culture to tourists”. These two aspects seem to be mutually exclusive at first but this paper will show that a binary model of “culture vs. commerce” does not provide an adequate conceptual framework to fully understand the complexities of culture.